2005
DOI: 10.1007/s00125-005-1938-5
|View full text |Cite
|
Sign up to set email alerts
|

Improved fibrinolysis by an intensive lifestyle intervention in subjects with impaired glucose tolerance. The Finnish Diabetes Prevention Study

Abstract: Aims/hypothesis: The aim of this study was to investigate the effects of lifestyle intervention on the levels of plasminogen activator inhibitor (PAI-1) and fibrinogen in subjects participating in the Finnish Diabetes Prevention Study (DPS). Methods: In five DPS centres, 321 subjects with impaired glucose tolerance (intervention group, n= 163; control group, n=158) had their PAI-1 and fibrinogen levels measured at baseline and at the 1-year follow-up. Additional 3-year follow-up assessments were carried out in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 50 publications
4
24
2
2
Order By: Relevance
“…Similar results have been reported for a 5 week soy-diet intervention in renal transplant patients [30]. While trials designed to produce weight loss describe associated reductions in plasma PAI-1 concentrations [31,32], more specific dietary interventions (for example, with fatty acids or Mediterranean diet) have generally failed to alter either fibrinolytic parameters or circulating vWF levels [33,34]. When 112 volunteers at increased cardiovascular risk were randomised to a low-fat or Mediterranean diet for 3 months, significantly reduced concentrations of plasma sICAM-1 and sVCAM-1 were observed in the latter group [35].…”
Section: Discussionsupporting
confidence: 69%
“…Similar results have been reported for a 5 week soy-diet intervention in renal transplant patients [30]. While trials designed to produce weight loss describe associated reductions in plasma PAI-1 concentrations [31,32], more specific dietary interventions (for example, with fatty acids or Mediterranean diet) have generally failed to alter either fibrinolytic parameters or circulating vWF levels [33,34]. When 112 volunteers at increased cardiovascular risk were randomised to a low-fat or Mediterranean diet for 3 months, significantly reduced concentrations of plasma sICAM-1 and sVCAM-1 were observed in the latter group [35].…”
Section: Discussionsupporting
confidence: 69%
“…[205][206][207][208][209][210][211][212][213][214][215][216][217][218][219] Description and quality of trial This RCT of 523 participants with IGT in Finland compared intensive lifestyle intervention with a control group. Participants were recruited by screening high-risk individuals (e.g.…”
Section: The Finnish Diabetes Prevention Studymentioning
confidence: 99%
“…A reduction in fibrinolytic activity is thought to increase CVD. Hamalainen et al (2005) 206 reported that in five centres improvement in fibrinolytic activity was seen by 1 year [31% reduction in plasminogen activator inhibitor-1 (PAI-1)]. 206 In one centre (Turku) it was measured again at 3 years and was shown to persist.…”
mentioning
confidence: 99%
“…There is probable evidence that the increase in FVIIa is greater following meals rich in MUFA (oleic acid) than for some sources of SFA [Sanders et al, 2000[Sanders et al, , 2006bTholstrup et al, 2003;Sanders and Berry, 2005;Berry et al, 2007a, b]. There is insufficient evidence to demonstrate chronic effects of different types of fatty acids on fibrinogen or fibrinolytic activity [Miller, 2005;Sanders et al, 2006b], but fibrinolytic activity improves with intensive lifestyle intervention (weight reduction and increased physical activity) [Hamalainen et al, 2005].…”
Section: Procoagulant and Fibrinolytic Activitymentioning
confidence: 99%